THE STRATEGY TO IMPROVE THE QUALITY OF LIFE AMONG HEROIN ADDICTS THROUGH METHADONE MAINTENANCE THERAPY - Eka Yuliartiningsih; Puput Oktamianti (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Many cases of heroin abuse was the leading cause of death. Due to difficulties stop addiction to heroin, many methods were used for the recovery process. The effective and approved therapy method with a medical approach was transferal heroin with another substance program, which was called methadone maintenance therapy. Methadone was chosen as the main substitution therapy because it has a similar effect to heroin with lengthier bioavailability, so it could be prescribed once a day. There are positive benefits that can make heroin addicts function normally with methadone maintenance therapy, it will improve the quality of life people with heroin addicts. Methods: This research used a narrative review method with data retrieval from Universitas Indonesia online database such as PubMed and Springer Link. The research strategy has done by employed several articles about life quality improvement of heroin addicts with methadone maintenance therapy service, which already publish in Universitas Indonesia online database in December 2017. The chosen articles were use, selected by inclusion criteria and exclusion criteria. Results: From the reviewed the 5 published journal articles, revealed one of the benefits from methadone maintenance therapy services is improving the life quality of heroin addicts. Conclusions: Methadone maintenance therapy services could improve the life quality of heroin addicts.